THE IMPACTS OF DATA INACCURACY ON RETAILER'S PERISHABLE INVENTORY - Bal, Mert; Ustundag, Alp (DIME UNIV GENOA, 2012)
Since perishable products such as fresh produce, dairy and meat have a finite usable lifetime and constitute more than a third of the worldwide sales at grocery retailers, controlling the inventories of these products is increasingly important. Without alignment of physical inventory and information system inventory, inventory information becomes inaccurate due to product spoilage and the retailer cannot take efficient inventory decisions. The purpose of this research is to investigate how the data inaccuracy affects the retailer's inventory performance for different levels of product lifetime, uncertainty of demand and lead time. Using a simulation model, the lost sales, product spoilage, average inventory and order quantities are calculated to investigate the retailer's performance over a 365 day period and ANOVA analysis is performed to examine the results.
Keywords: Perishable; Product lifetime; Inventory; Simulation; Data inaccuracy; DETERIORATING INVENTORY; SUPPLY CHAIN; POSTPONEMENT STRATEGY; PERMISSIBLE DELAY; SINGLE-VENDOR; EOQ MODEL; PRODUCTS; SYSTEM; POLICY; TIMES; Engineering; Operations Research & Management Science